Integrasi Nilai-Nilai Hindu dalam Pembelajaran IPA Guna Meningkatkan Kecerdasan Spiritual Siswa Sekolah Dasar - Asta Mariyana, Nyoman Selvia; Lestari, Ika; Usman, Herlina (Cetta: Jurnal Ilmu Pendidikan, 2025)
Spiritual intelligence is an essential dimension in the development of students' character, encompassing the meaning of life, moral values, and spiritual relationships with God, others, and nature. Science education (IPA), which has traditionally been neutral toward religious values, in fact holds great potential for integration with spiritual values, particularly within the context of Hindu education. This study aims to examine the integration of Hindu values into science learning as a strategy to foster spiritual intelligence among elementary students at Adi Widyalaya. The method used is a literature review, analyzing various scientific sources and Hindu scriptures to explore the relationship between scientific concepts and values such as Tri Hita Karana, Rwa Bhineda, Ahimsa, Panca Maha Bhuta, and Karma Phala. The findings indicate that integrating these values not only enhances scientific understanding but also cultivates empathy, moral responsibility, and spiritual awareness toward nature. This study contributes scientifically by offering a conceptual framework that integrates science and Hindu spirituality, and practically by providing a foundation for developing science curricula and teaching materials that align with the characteristics of Widyalaya, in support of holistic and transformative education.